"DOS ÚTEIS EFFEITOS DA SOCIABILIDADE E DAS VANTAGENS DA CIVILISAÇÃO": A questão indígena e sua representatividade nos gabinetes provinciais do Rio Grande do Sul (1846-1870) - Bringmann, Sandor Fernndo (Outros Tempos: Pesquisa em Foco - História, 2011)
In this paper we discuss some issues concerning at representation of speeches by provincialauthorities  of  Rio  Grande  do  Sul,  forward the  process  of  "civilization"  and  catechesis of  theindigenous group Kaingang, inhabitants of the north and northeast of the province. Through theanalysis of documentary and textual sources we seek to reveal the hegemonic representation on theKaingang and identify how the established stereotypes will influence the actions of the provincialgovernment, either to pacify the natives through strategies of attraction, either to control their attemptsat resistance to the government project.